Impact of the COVID-19 pandemic on small and medium-sized enterprise (SME) government suppliers involved in government green procurement (GGP) - Masron, Nurin Athilah; Zainol, Zaini; Ismail, Suhaiza (Emerald Publishing Limited, 2026)
Purpose The objectives of this paper are twofold. First, it aims to investigate the impact of the COVID-19 pandemic on the activities and performance of small and medium-sized enterprises (SMEs) government suppliers involved in government green procurement (GGP). Second, it examines the differences in the impact of COVID-19 between small and medium-sized groups. Design/methodology/approach The study used a questionnaire survey that was distributed to SMEs listed in the MyHIJAU directory that supply green goods and services to the government. Of the total 394 sample respondents, 126 usable questionnaires were received, representing a usable response rate of 31.98%. Descriptive analysis of mean score, standard deviation and mean score ranking was used to analyse the overall results. A t-test analysis was carried out to examine the differences between the small and medium-sized groups of companies. Findings The study discovers that the SME government suppliers involved in GGP were impacted by the COVID-19 pandemic. The top ranked impacts are that “the COVID-19 pandemic has heightened health and safety practices among the employees”, “the COVID-19 pandemic has reduced company’s turnover”, “the COVID-19 pandemic has forced the company to implement a cost reduction strategy”, “the COVID-19 pandemic has had a negative impact on the company’s ability to deliver work, supplies or services to the government” and “the COVID-19 pandemic has forced the company to incur higher production costs for green products or services provided”. However, there is no significant difference between the impact of the COVID-19 pandemic on the small and medium-sized group of enterprises. Originality/value The present study is among the fewer studies on the impact of the COVID-19 pandemic, with particular focus on SME government suppliers involved in GGP